2019
DOI: 10.1504/ijlt.2019.100613
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tablet PCs on learning outcomes in a classroom environment

Abstract: It is evident that information and communication technology (ICT) plays a vital role in educational settings. However, it is also important to determine how learners use ICT in different settings. Currently, ICT is mostly used as a supporting tool for the existing learning process, however, it is still unable to revolutionise the learning and teaching process. The reason for this can be its failure to unleash its original potential and capabilities. This study adopted a quasi-experimental method to measure the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…The authors suggest that a thoughtful integration of technology, grounded in an understanding of its advantages and limitations, can significantly impact students' psychological and educational performance. Javed and Samara (2019) conducted a quasi-experimental study to assess the impact of tablet PCs on learning outcomes in classroom settings. Their findings indicate that students who utilized tablet PCs exhibited better learning outcomes compared to those who did not use these devices.…”
Section: Impact On Learning Outcomesmentioning
confidence: 99%
“…The authors suggest that a thoughtful integration of technology, grounded in an understanding of its advantages and limitations, can significantly impact students' psychological and educational performance. Javed and Samara (2019) conducted a quasi-experimental study to assess the impact of tablet PCs on learning outcomes in classroom settings. Their findings indicate that students who utilized tablet PCs exhibited better learning outcomes compared to those who did not use these devices.…”
Section: Impact On Learning Outcomesmentioning
confidence: 99%
“…Respecto a la evidencia del uso de aplicaciones en el aprendizaje, se observa un impacto significativo en la adquisición de conocimientos generales (Javed y Samara, 2019). En el aprendizaje de inglés, se ha mostrado que el uso de aplicaciones favorece mayores logros y reducción de ansiedad en el aprendizaje (Cheng y Chen, 2019).…”
Section: Estudios Cuasiexperimentalesunclassified
“…While TBLT and VLEs have shown potential in improving language learning outcomes, there are mixed results regarding the effectiveness of mobile technology devices in language learning. Some studies have reported positive effects of tablet use on various aspects of student learning, including learning outcomes, reading, literacy, phonological awareness, vocabulary, and writing skills (Aliagas & Margallo 2017;Dunn & Sweeney 2018;Javed & Samara 2019;Zhang & Quinn 2020). However, other studies have reported negative results in terms of learning achievement, participation, and knowledge comprehension (Aspiranti et al 2022;Zhu & Levesque 2021).…”
Section: Literature Reviewmentioning
confidence: 99%